2022
DOI: 10.1039/d2qm00077f
|View full text |Cite
|
Sign up to set email alerts
|

A recyclable covalent triazine framework-supported iridium(iii) terpyridine complex for the acceptorless dehydrogenative coupling of o-aminobenzyl alcohols with ketones to form quinolines

Abstract: A cyclometalated iridium(III) complex Ir(tpy)@CTF, which is designed and synthesized by the coordinative immobilization of [Ir(tpy)Cl3] on a functionalized covalent triazing framework, was proven to be a highly effective for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Fujita and Yamaguichi et al have designed a series of Cp*Ir complexes bearing a bipyridonate ligand or an α-hydroxybipyridine ligand, which exhibited unique catalytic activity for acceptor-less dehydrogenation of N-heterocycles and alcohols and hydrogen production from an alcohol–water solution based on ligand-promoted dehydrogenation. We have also reported that such complexes are general catalysts for acceptor-less dehydrogenative cyclization , and hydrogen autotransfer process and have developed a series of new metal–ligand bifunctional catalysts. As a continuing effort in the development of catalytic transformations, we turn our research from organic synthesis to renewable energy. Herein, we wish to describe the design and synthesis of a new type of Cp*Ir complex bearing a 2,2′-carbonylbibenzimidazole (2,2′-COBiBzImH 2 ) ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Fujita and Yamaguichi et al have designed a series of Cp*Ir complexes bearing a bipyridonate ligand or an α-hydroxybipyridine ligand, which exhibited unique catalytic activity for acceptor-less dehydrogenation of N-heterocycles and alcohols and hydrogen production from an alcohol–water solution based on ligand-promoted dehydrogenation. We have also reported that such complexes are general catalysts for acceptor-less dehydrogenative cyclization , and hydrogen autotransfer process and have developed a series of new metal–ligand bifunctional catalysts. As a continuing effort in the development of catalytic transformations, we turn our research from organic synthesis to renewable energy. Herein, we wish to describe the design and synthesis of a new type of Cp*Ir complex bearing a 2,2′-carbonylbibenzimidazole (2,2′-COBiBzImH 2 ) ligand.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, acceptorless dehydrogenation, borrowing hydrogen, and transfer hydrogenation strategies have gained popularity to overcome these challenges [15,16] . Owing to this, there are numerous reports on acceptorless dehydrogenative synthesis of quinolines utilizing homogenous catalytic system involving metals such as Co, [17] Cu, [18] Ir, [19] Fe, [20] Mn, [21] Ni, [22] Re, [23] Ru, [24] Zn, [25] and heterogeneous catalyst such as Co on C 3 N 4 , [26] CuO, [27] CuNiFeO, [28] Fe 2 O 3 , [29] CoFe 2 O 4 , [30] Ir on mesoporous silica, [31a] porous organic polymer supported Ir catalyst, [31b] covalent triazine framework supported Ir complex, [31c] Pd on polymer support [32] . However, the synthesis of quinoline via transfer hydrogenation strategy remains less explored [33–36] .…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a series of environmentally friendly transformations based on hydrogen (or deuterium) autotransfer processes 13 or acceptorless dehydrogenation. 14 In particular, we demonstrated the selective N -alkylation of aminobenzenesulfonamides with alcohols to amino-( N -alkyl)benzenesulfonamides catalyzed by a homogeneous iridium catalyst [Cp*IrCl 2 ] 2 . 15 This reaction exhibited the unique potential of hydrogen auto-transfer processes, which could recognize different types of amino groups in the N -alkylation of complex molecules.…”
Section: Introductionmentioning
confidence: 99%